Reproductive behavior of the marine gastropod Charonia seguenzae (Aradas & Benoit, 1870) in captivity - DOXA, CHRYSA K.; STERIOTI, ASPASIA; DIVANACH, PASCAL; KENTOURI, MAROUDIO (Mediterranean Marine Science, 2019)
The reproductive behavior of the gastropod Charonia seguenzae (Aradas & Benoit, 1870) was studied through the description of 19 copulation and 21 egg laying events of 134 wild individuals. Findings in the present study regarding a part of the reproduction temperature range (20 to 23oC) and the demonstration of maternal care provided important information on their biology, behavior and ecology. Furthermore, observed polyandry by the females and collaborative care of embryonic sacks, were two aspects of the species reproductive biology that pose new questions both at ecological and evolutionary level.